Harmonic Scalpel and Electrothermal Bipolar Vessel Sealing System in Head and Neck Surgery: A Prospective Study on Tissue Heating and Histological Damage on Nerves. (November 2015) - Tirelli, Giancarlo; Camilot, Debora; Bonini, Pierluigi; Del Piero, Giulia Carolina; Biasotto, Matteo; Quatela, Eliana
Objectives: Define and compare the thermal nerve injury caused by 3 different vessel sealing and dissection devices: the harmonic scalpel (HS), the electrothermal bipolar vessel sealing system (EBVS), and the bipolar electrosurgery unit (BE). Methods: First we recorded the heating variations in pig tissue caused by a BE unit, HS, and EBVS after an activation for 5, 10, and 15 seconds at minimum and at maximum power. In the second part, we evaluated the histological damage caused by HS and EBVS on 20 in vivo human nerves, 10 per device. The 2 scalpels were placed and activated at 3 different distances from the nerve (1, 3, and 5 mm). The extension and the degree of the nerve lesion was then calculated. Results: The instrument determining the highest rise in temperature was the BE unit, followed by HS and then EBVS. Comparison between the extension and degree of nerve injury caused by the 2 scalpels showed no statistically significant differences. Based on these evaluations, we established a relative safety limit at 3 mm and an absolute safety limit at 5 mm for both scalpels. Conclusions: Our data suggest EBVS and HS can be considered valid and safe devices for ENT surgery.